Exploring the Impact of Slang Usage Among Students on WhatsApp: A Dig-ital Linguistic Analysis - Manurung, Jonson; Napitupulu, Merlin Helentina; Simangunsong, Humala (Jurnal Ilmu Pendidikan dan Humaniora, 2022)
This research delves into the dynamic world of informal language usage among students on the popular messaging platform, WhatsApp. As digital communication becomes an integral part of daily life, the study examines the frequency, variability, motivations, and social dynamics of slang usage among students. Through surveys, interviews, and, where possible, data analysis of WhatsApp conversations, the research uncovers the complex interplay between language, technology, and human connection in the digital realm. The findings reveal that slang is not merely a linguistic phenomenon but a reflection of the adaptability of language in the digital age. It serves as a linguistic bridge that enables informal communication in digital interactions. The lexicon of slang is diverse and ever-evolving, reflecting the cultural and social context in which it thrives. Motivations for slang usage go beyond humor and informality, extending to self-expression, emotional connection, and the formation of digital identities. Slang enhances social bonds and fosters a sense of belonging among peers, shaping the quality of digital interactions. Demographic variations in slang usage demonstrate its context-dependent nature, influenced by factors such as age, gender, and geographical location. Slang's impact on digital communication is significant, enhancing informal exchanges while presenting challenges, particularly in cross-cultural interactions. This research underscores the importance of digital literacy and cross-cultural understanding in online interactions and has implications for education, linguistic research, and cross-cultural communication. As the digital landscape continues to evolve, this research offers a deeper understanding of the role of language in shaping human connections in the digital age. It calls for ongoing exploration into the ever-changing linguistic dynamics of digital communication and its profound impact on contemporary society.